Śrī Samartha caritra - Ājag̃āvakara, Jagannātha Raghunātha, 1879-1955 (SAMP early 20th-century Indian books project ;, 1935)
Biography of Rāmadāsa, b. 1608, religious leader and founder of Samartha Sampradaya.